Intraoperative Hardware Failure of the Fassier–Duval Rescue System in a Pediatric Patient with Osteogenesis Imperfecta - Michael E. Kahan; Nathan R. Angerett; Jill C. Flanagan (Case Reports in Pediatrics)
The use of telescopic intramedullary rods for the treatment of lower extremity deformity in children with osteogenesis imperfecta has been well described. The reinforcement of these weakened weightbearing bones with intramedullary devices leads to improvements in mobility that progress into adulthood. Although the current telescopic intramedullary rod systems are an upgrade from earlier systems, they are still associated with high rates of reoperation and complication. We describe a unique complication encountered during a revision which involved the male retriever system for the Fassier–Duval rod (FDR) (Pega Medical, Quebec, CA) experienced intraoperatively. To our knowledge, this mechanism of failure has not been previously described in the literature.